The effect of an intermediate layer of flowable composite resin on microleakage in packable composite restorations - D. ZISKIND, I. ADELL, E. TEPEROVICH, & B. PERETZ (Paediatric Dentistry, 2005)
The aim of the present study was to evaluate the effect of a thin layer of flowable composite on microleakage in Class II direct packable composite resin restorations on young permanent teethin vitro.